Audit on operating theatres in Sri Lanka - Thevanesam, Vasanthi; Elvitigala, Jayanthi; Liyanapathirana, Veranja (International Journal of Infection Control, 2010)
Design and behavior within a theatre is important in preventing infections at surgical sites. Protocols exist for theatre infection control starting from the design stage. Compliance of theatres in the Sri Lankan public health sector to such recommendations was assessed in this audit in a questionnaire based descriptive study conducted in relation to a theatre infection control workshop. Design, location, layout, ventilation, personal management in the theatres were assessed. Sri Lankan theaters fall below the recognized standards in both theatre design and infection control practices and much needs to be improved to bring up the standards of the theatres in the system to internationally acceptable norms.